STUDI KOMPARATIF TENTANG ZAKAT TANAH SEWAAN MENURUT PANDANGAN ISLAM - Putri Nabila Masduki; Ashif Az Zafi (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
A direct order from Allah stated in his kalam namely Al-Qur’an and included the fourth pillar of Islam is zakat. Allah rules those who are able to pay zakat and give it to those who are entitled to receive or mustahiqqin. There are some assets that must be subject to zakat, one of them is zakat rented land. The obligation of zakat on rented land is a difference of opinion among the scholars, including among them who is obliged to pay zakat on leased land. In this application there is still a debate between land owners or land tenants. Imam Hanafi and the ulama 'hanafiyyah are the obligations of the renting party, while Imam Syafi'i and the Syafi'i ulama are of the opinion of the tenant's obligation, this has the opportunity to be compared.